Better tolerance to Huanglongbing is conferred by tetraploid Swingle citrumelo rootstock and is influenced by the ploidy of the scion - Sivager, Gary; Calvez, Leny; Bruyere, Saturnin; Boisne-Noc, Rosiane; Hufnagel, Barbara; Cebrian-Torrejon, Gerardo; Doménech-Carbó, Antonio; Gros, Olivier; Ollitrault, Patrick; Morillon, Raphaël (Frontiers in Plant Science, 2022)
Huanglongbing (HLB) is a disease that is responsible for the death of millions of trees worldwide. The bacterial causal agent belongs to Candidatus Liberibacter spp., which is transmitted by psyllids. The bacterium lead most of the time to a reaction of the tree associated with callose synthesis at the phloem sieve plate. Thus, the obstruction of pores providing connections between adjacent sieve elements will limit the symplastic transport of the sugars and starches synthesized through photosynthesis. In the present article, we investigated the impact of the use of tetraploid Swingle citrumelo (Citrus sinensis [L.] Osbeck Citrus paradisi Macfrad × Poncirus trifoliata [L.] Raf) rootstock on HLB tolerance, compared to its respective diploid. HLB-infected diploid and tetraploid rootstocks were investigated when grafted with Mexican and Persian limes. Secondary roots were anatomically studied using scanning electron microscopy (SEM) and transmission electron microscopy (TEM) to observe callose deposition at the phloem sieve plate and to evaluate the impact of the bacterium’s presence at the cellular level. Voltammetry of immobilized microparticles (VIMP) in roots was applied to determine the oxidative stress status of root samples. In the field, Mexican and Persian lime leaves of trees grafted onto tetraploid rootstock presented less symptoms of HLB. Anatomical analysis showed much stronger secondary root degradation in diploid rootstock, compared to tetraploid rootstock. Analysis of the root sieve plate in control root samples showed that pores were approximately 1.8-fold larger in tetraploid Swingle citrumelo than in its respective diploid. SEM analyses of root samples did not reveal any callose deposition into pores of diploid and tetraploid genotypes. VIMP showed limited oxidative stress in tetraploid samples, compared to diploid ones. These results were even strongly enhanced when rootstocks were grafted with Persian limes, compared to Mexican limes, which was corroborated by stronger polyphenol contents. TEM analysis showed that the bacteria was present in both ploidy root samples with no major impacts detected on cell walls or cell structures. These results reveal that tetraploid Swingle citrumelo rootstocks confers better tolerance to HLB than diploid. Additionally, an even stronger tolerance is achieved when a the triploid Persian lime scion is associated.